Salt-Taste Polymorphism TRPV1-rs8065080 Is Associated with Increased Likelihood of Depression in an Elderly Cohort - Celeste Ferraris; Christopher J. Scarlett; Martin Veysey; Mark Lucock; Tamara Bucher; Emma L. Beckett (Lifestyle Genomics, 2023)
Introduction: Despite the prevalence of depression and anxiety worldwide, their aetiologies remain unclear, and they can be difficult to diagnose and treat. Changes in salt-taste perception have been found in both conditions. Single-nucleotide polymorphisms (SNPs) in the salt-taste-related gene, TRPV1, have been associated with alterations to salt-taste perception, preference, and sodium consumption. Diet quality is a known modifier of depression and anxiety and recently, sodium intake has been studied in mental health. However, the relationships between salt-taste genetics, depression, anxiety, and these dietary factors are yet to be elucidated. Methods: Data from the well-characterized cross-sectional Retirement Health and Lifestyle Study (n = 536, ≥65 y) were used to explore the relationships between the salt-taste SNP TRPV1-rs8065080, levels of depression and anxiety (Hospital Anxiety and Depression Scale, HADS), estimated sodium intake, and diet quality in this secondary analysis. Standard least-squares regression and nominal logistic regression modelling were used to compare continuous and categorical variables, respectively, with analyses stratified by sex. Results: Presence of the TRPV1-rs8065080 variant allele (C) was found to increase the likelihood of having depression (HADS) in the total population and in males. The associations remained significant after adjusting for sodium intake, three diet quality indices, and demographic variables, suggesting that TRPV1-rs8065080 genotype is driving the association with depression. Discussion/Conclusion: Future studies should explore extra-oral functions of the SNP and salt-taste receptors in the brain and the roles of neurotransmitters common to both depression and salt taste to improve the management of this increasingly prevalent and difficult-to-treat condition.